Contemporary challenges of museum communication: сultivating Soft Skills for Urban Sustainability - Anastasia Belolutskaya; Ivan Grinko (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2025)
Heritage is one of the elements of sustainable development of territories. Due to its fragility, it requires constant attention from the community. It is essential to clearly articulate the practical significance of heritage for communities to maintain their motivation. One way to practically use heritage is to integrate it into programs for developing soft skills in children and adults. Moscow City University conducted a study of 40 museums and significant cultural street objects to answer the question of what conditions have been created for the development of citizens' thinking and communication. Methods: parametric scale assessment, observation, interviews, focus groups. Findings: the main deficits include working with contradictions, multi-positioning, personal narratives, social reflection, as well as creativity and imagination. Wider implications: creating a tool for organizations working with heritage for comprehensive parametric assessment of historical urban landscapes in different countries in terms of their impact on the soft skills of citizens.